[Image 27] - Smith, Captain Sir William [?ob. 1732] (My University, 1804)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of an Old Castle and battery for covering the ferry across an inlet from Mulray on the direct road to [indecipherable] by Sir Wm Smith 1804.
Keywords: Mulray; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Castles in art; Landscapes (Representations) 1800-1810